Consumer preference, growth and profitability of African catfish (Clarias gariepinus) grown in treated and aerated wastewater fed ponds in Kumasi, Ghana - Sey, S. E.; Agbo, N.W.; Edziyie, R.; Amoah, Philip; Yeboah-Agyepong, M.; Nsiah-Gyambibi, R.; Abbas, S. (Elsevier, 2021)
Recycling of wastewater provides a substantial solution to the global issue of water scarcity and high water use in aquaculture. However, this sustainable way of wastewater use has not been given much attention and exploration. This study focused on the consumer preference for fish grown in treated wastewater as well as the effect of aeration on the growth performance and economic benefit of African catfish (Clarias gariepinus) grown in treated wastewater. Two hundred (200) respondents from two communities (Chirapatre and Gyinyase) near the wastewater treatment plant in Kumasi were interviewed to determine their willingness to accept and pay for African catfish grown in treated wastewater. For the growth trial, a total of 600 fish (of average initial weight 39.12g) were stocked in two maturation ponds with 4 h (3:00am–7:00am) of aeration daily. The trial lasted for 12 weeks and variables monitored included the survival, growth performance (weight gain, specific growth rate, and yield) and water quality. Fish cultured in non-aerated wastewater ponds (NWFPs) under similar conditions as in aerated wastewater-fed ponds (AWFPs) served as control. The results indicated most important considerations for consumers in their choice of fish to consume were in order of importance; food safety, freshness of fish, taste and packaging. The proximity of consumers to the treatment plant, the price of fish, religion, and age and whether or not they were fish consumers affected their willingness to pay for African catfish grown in the treated wastewater significantly. For the growth trial, dissolved oxygen concentrations in the aerated ponds were significantly higher than in the NWFPs and this led to more than a doubling of the growth rates in the African catfish grown in the AWFPs (189.10g 11.32) as compared to the NWFPs (90.70g 11.59). The pond aeration improved fish growth significantly (p < 0.0098). On economic benefit, the aerated system yielded profits of 618.83 (€103.13) as compared to a loss of 104.99 (€17.50), which was incurred in the non-aerated ponds. Education of the consumers on the process of wastewater treatment and establishment of food safety guidelines will therefore be recommended to increase consumer interest in consuming fish from the treated wastewater.